Thermal, spectroscopic and biological studies on solid ibuprofen complexes of heavy trivalent lanthanides and yttrium - Holanda, Bruno B.C. [UNESP]; Guerra, Renan B. [UNESP]; Legendre, Alexandre O. [UNESP]; Almeida, Débora F. [UNESP]; Fraga-Silva, Thais F.C. [UNESP]; Finato, Ângela C. [UNESP]; Venturini, James [UNESP]; Bannach, Gilbert [UNESP] (Elsevier, 2017)
Heavy lanthanide complexes (Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu) and yttrium (III) complexes with ibuprofen ligands (Hibu) were synthesized and characterized by simultaneous thermogravimetric and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), attenuated total reflection mid-infrared spectroscopy (ATR-MIR), complexometric titration, X-ray powder diffraction (XRD) in order to determine stoichiometry, thermal stability and the ligand coordination modes of the compounds. The volatiles released were also analyzed by online coupled thermogravimetry-infrared spectroscopy evolved gas analysis (TG-EGA-MIR), to identify the main product resulting from the heating of terbium complex. In addition, ibuprofen and the synthesized compounds were tested to assess cytotoxic/proliferative and anti-inflammatory activity. The results of the cytotoxicity assays showed that compounds [Yb(ibu)3], [Lu(ibu)3] and [Y(ibu)3] decreased the cytotoxic activity of ibuprofen. Furthermore, [Yb(ibu)3] and [Lu(ibu)3] exhibited a significant anti-inflammatory profile, superior to that of ibuprofen. Under the stimulatory effect of lipopolysaccharide, these compounds displayed anti-inflammatory activity characterized by low TNF-α and H2O2 production and high IL-10 production, emerging as interesting alternatives for further biological applications.
Keywords: Biological studies; Lanthanides; Metallodrug; Middle infrared spectroscopy; TG-EGA-MIR; Thermal behavior